(untitled) (Research, Society and Development, 2023)
Intraoral scanning is a viable alternative to be used in implant dentistry. However, the use of this technique is more in evidence in recent years and there is a need for a survey of studies to establish an indication protocol for the correct use of scanners and digital molding. Therefore, this study aims to conduct a systematic review with meta-analysis (Cochrane model; PRISMA and PROSPERO: CRD42022313310), in order to analyze the primary studies that evaluated techniques used to obtain moldings in single and partial fixed cases in implant dentistry, using the intraoral scanning system (intervention) compared to the conventional molding system for implant-supported prostheses (comparison). The PubMed/Medline, Cochrane Collaboration, Web of Science and SciELO databases were analyzed using area keywords. The collected data were tabulated and organized qualitatively. Clinical trials were classified according to hierarchy scales. The main results indicated the feasibility of digital scanning when compared to the conventional molding technique for making implant-supported prostheses. In addition, digital flow was associated with shorter clinical procedure time, when compared to conventional molding, greater satisfaction of patients. It is concluded that there is feasibility in the indication and use of intraoral scanning systems to obtain single and multiple implant-supported fixed prostheses. However, no differences were identified between conventional flow vs. digital flow regarding complications and/or failures of prostheses.